A New Neuropathologic Mechanism of Blood pH Irregularities After Neck Trauma: Importance of Carotid Body-Glossopharyngeal Nerve Network Degeneration - Cakir, Tayfun; Kayaci, Selim; Aydin, Mehmet Dumlu; Ozoner, Baris; Calik, Ilknur; Altinkaynak, Konca (Elsevier Science Inc, 2019)
OBJECTIVE: We created a neck trauma model by injecting blood into the sheath of rabbits' carotid bodies (CBs). Then we determined the relationship between neuronal degeneration of the CB due to hemorrhage of this organ and its clinical effects such as blood pH and heart rhythm. METHODS: The present study included 24 adult male New Zealand rabbits. The animals were divided into 3 groups: control (n = 5); sham (0.5 mL saline injected into CBs; n = 5); and study (CB trauma model; n = 14). pH values and heart rhythms were recorded before the experiment to determine the values under normal conditions, and measurements were repeated thrice in the days following the experiment. The number of normal and degenerated neuron density of CBs was counted. The relationship between the blood pH values, heart rhythms, and degenerated neuron densities was analyzed. RESULTS: Heart rhythms were 218 +/- 20 in the control group, 197 +/- 16 in the sham group (P = 0.09), and 167 +/- 13 in the study group (P < 0.0005). pH values were 7.40 +/- 0.041 in the control group, 7.321 +/- 0.062 in the sham group (P = 0.203), and 7.23 +/- 0.02 in study group (P < 0.0005). Degenerated neuron densities were 12 +/- 4/mm(3) in the control group, 430 +/- 74/mm(3) in the sham group (P < 0.005), and 7434 +/- 810/mm(3) in the study group (P < 0.0001). CONCLUSIONS: A high degenerate neuron density in the CB can decrease blood pH and hearth rhythm after neck trauma, and there might be a close relationship between the number of degenerated neurons and clinical findings (such as heart rhythm and blood pH). This relationship suggests that injury to the glossopharyngeal nerve-CB network can cause acidosis by disturbing the breathing-circulating reflex and results in respiratory acidosis.
Keywords: Blood pH; Carotid body; Glossopharyngeal nerve; Neck trauma